Description of the male Perucania longiareola New & Thornton (Psocoptera: Ptiloneuridae) - García Aldrete, Alfonso Neri (Instituto de Ecología, A.C., 1998)
The male Perucania longiareola New & Thornton is described and iilustrated. It was taken at the type locality, in the Rio Tambopata Reserved Zone (Madre de Dios, Perú, 12°50’ S, 69°20' W). The specimen studied will be deposited in the Smithsonian Institution Collection, Washington, D.C. (U.S.A.).